STRATEGI MANAJEMEN DATA PRIVASI DALAM ERA DIGITAL PADA PERUSAHAAN DAN BISNIS MODERN - Zahfira Halim; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this study is to analyze the data privacy management strategies implemented by modern companies and businesses in addressing the challenges of the digital era. This research adopts a descriptive qualitative method using a library research approach, examining various academic sources, regulations, and corporate case studies. The findings reveal that effective data privacy management strategies include the implementation of clear internal policies, the use of security technologies such as encryption and multi-factor authentication, as well as regular audits and privacy education. Furthermore, transparency with consumers regarding the use of personal data plays a crucial role in building public trust. These findings highlight the importance of integrating policies, technology, and education as the main foundation for safeguarding data privacy in the digital age.